Predicting annual grassland productivity from community-level mean traits: how does a rapid method based on botanical survey perform? - Louault F.; Note P.; Carrère P.; Pottier J. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Because methodology used to assess functional structure of the community has to be adapted to the objectives of the study and the processes of interest, two simpler methods for measuring cumulated weighted mean values of three traits are compared, and the ability of the functional descriptors to predict the annual aboveground production tested on a set of 28 grassland plots. The non-destructive method, applied once a year and based on botanical survey to assess the species abundances, provides cumulated weighted mean (CWM) values that are highly correlated to values resulting from the reference method, that is from species hand sorting of biomass sampled all along the year to assess annual productivity. Statistical models predicting annual production using the CWM of leaf traits and plant height showed good to very good fits, are highly significant, with r² of 72.4 for the reference method and 63.7 for the simplest one. This latter is thus considered highly valuable for studying links between functional structure and processes.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)